The study of Relation between Cultural Components and National Attachment among Citizens of Yazd city. - M. Farahmand; M. Damanbagh (Taḥqīqāt-i Farhangī-i Īrān, 2017)
National attachment sense as one of the components of social Property is a key word in national culture. Any definition of society is Occurred by accepting attachment and commitment sense and the society is existed to some extent because people have positive sense about that. National attachment sense is considered as one the important affairs of any society and its proper recognition and full knowledge of authorities and affair operators about the effective social factors on that can be an effective step in recognizing the existent problems in society. The present research reviewed the relation between cultural components and national attachment among the Yazd citizens. The research statistical society was all of the Yazd’s 15 to 65 years old citizens that 384 people were selected as sample by Cochran formula. The tool of data gathering was researcher-made questionnaire that had appropriate validity and reliability. Sampling method has been multi-stage clustered. Results showed that there was a meaningful relationship between secularization, consumerism and virtual social networks with national attachment has been reverse and meaningful, but the relationship between age and values preferences with national attachment has been direct and meaningful. Independent variables in regression equation managed to explain 39 percent of national attachment variable changes. The greatest impact on dependent variable (national attachment) has belonged to the variables of secularization, age, values preferences and consumerism.